2013
DOI: 10.1038/protex.2013.068
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite based flexible ultrasensitive resistive gas sensor for chemical reactions studies

Abstract: Room temperature operation, low detection limit and fast response time are highly desirable for a wide range of gas sensing applications. However, the available gas sensors suffer mainly from high temperature operation or external stimulation for response/recovery. Here, we report an ultrasensitive-flexiblesilver-nanoparticle based nanocomposite resistive sensor for ammonia detection and established the sensing mechanism. We show that the nanocomposite can detect ammonia as low as 500 parts-per-trillion at roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…2 b-i reveals two linear regions, one between 0 and 50 ppmv and another linearity between 50 and 100 ppmv. The two linear capacitive response domains likely correspond to different mechanisms of ammonia adsorption onto the C-dot-IDE surface; indeed, distinct NH 3 concentration-dependent surface-adsorption regimes have been reported, indicating NH 3 monolayer formation in low concentrations, multilayer assembly in higher ammonia concentrations [ 34 36 ]. In the case of exposure of the red C-dot-IDE sensor to DMF, a single linear dependence was apparent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 b-i reveals two linear regions, one between 0 and 50 ppmv and another linearity between 50 and 100 ppmv. The two linear capacitive response domains likely correspond to different mechanisms of ammonia adsorption onto the C-dot-IDE surface; indeed, distinct NH 3 concentration-dependent surface-adsorption regimes have been reported, indicating NH 3 monolayer formation in low concentrations, multilayer assembly in higher ammonia concentrations [ 34 36 ]. In the case of exposure of the red C-dot-IDE sensor to DMF, a single linear dependence was apparent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chemiresistive sensors have aroused much attention in environment monitoring, industry and agriculture production, medical diagnosis, military, and public safety, etc. nowadays [ 1 - 5 ]. In order to meet the requirements of industry and other fields' demands, semi-conducting metal oxide, organic semiconductors, and carbon materials, etc., which have high aspect ratio and large specific surface area, have been widely used as sensing materials and the excellent performances of the resultant devices have been achieved [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pandey et al [ 109 ] mentioned the typical features that a gas sensor should possess: (i) operation at room temperature; (ii) working in ambient environment and no requirement of oxygen or air supply; (iii) no external stimulus such as Joule heating or UV illumination for response/recovery; (iv) low detection limit; (v) high sensitivity and reproducibility; (vi) fast response and recovery; (vii) low cost and eco-friendly, etc. This list is extended enough, but some points may be added.…”
Section: Ammonia Gas Sensors and Gas Sensing Mechanismmentioning
confidence: 99%
“…The range of the concentrations of ammonia to be detected ranges from a few ppb to hundreds of ppm. However, some of the authors already reported the sensors are capable of detecting a few ppt (parts per trillion), e.g., guar gum/Ag nanocomposite film [ 109 ]. The sensors based on carbon nanomaterials approach this level.…”
Section: Ammonia Gas Sensors and Gas Sensing Mechanismmentioning
confidence: 99%